Children’s Coping Scale: psychometric properties - Morales Rodríguez, Francisco Manuel; Trianes Torres, María Victoria; Blanca Mena, María José; Miranda Páez, Jesús; Escobar Espejo, Milagros; Fernández Baena, Francisco Javier (Anales de Psicología / Annals of Psychology, 2012)
It is important to study coping among school-age children, as having coping skills is a key aspect of a healthy life. The aim of the present study was to construct and validate a coping scale for assessing the types of coping strategies used by primary school children in relation to four kinds of stressors. Participants were 402 boys and girls aged between 9 and 12 years. The paper reports the results of a confirmatory factor analysis and evidence of reliability and validity. The instrument comprises 35 self-report items that assess nine different coping strategies, distinguishing between problem-focused and non-productive coping. The results show that the scale has adequate psychometric properties for the assessment of children’s coping strategies.